Pengorbanan dan Jamuan Elisa Sebelum Mengikuti Elia: Historis Kritis 1 Raja-Raja 19:19-21 - Ruth Intan Sipahutar; Patricia Dwi Irwani Telaumbanua (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research aims to study the story of Elisha in 1 Kings 19:19-21, which describes God's call to Elisha to replace Elijah as a prophet. Elisha's action of burning his plow and slaughtering his oxen is understood to be a symbol of total sacrifice & commitment to leave his old life behind in order to follow God's call. This research uses a literature study method using Qualitative approach, analyzing biblical texts and related literature about the prophetic call & sacrifice in the Bible. The results of the analysis reveal that Elisha's actions reflect full commitment to God's call, which involves sacrifice not only materially as well as spiritually. Apart from that, Elisa's request to say goodbye to other people indicates the importance of balance between spiritual calling & human interaction. This research concludes that God's calling requires total sacrifice & commitment, but always pays attention to obligations towards family & society. It is hoped that the research output This can enable Christians to understand how to carry out God's call with full responsibility.